(untitled) (Nigerian Journal of Physiological Sciences, 2024)
The purpose of the present study was to investigate the ????-amylase and ????-glucosidase inhibitory potentials of 2-hydroxy-1,4-naphthoquinone (2HNQ). The inhibition of these two carbohydrates metabolizing enzyme was done by varying the concentrations of 2HNQ in the presence of α-amylase, α-glucosidase with starch and p-nitrophenylglucopyranoside (pNPG) respectively as their susbtrates. The mode of inhibitions of the two enzymes by 2HNQ was determined using double-reciprocal transformation. The result obtained indicated that 2HNQ inhibited ????-glucosidase activity with an IC50 0.260 mg/mL lowered than acarbose (1.530 mg/mL). Meanwhile, a moderate inhibitory potential of 2HNQ against ????-amylase was observed with an IC50 of 1.757 mg/mL compared with acarbose (IC50 of 3.600 mg/mL). Furthermore, 2HNQ amazingly mops up reactive oxygen species. The observed inhibitions of α-amylase and α-glucosidase activity as well as radical scavenging potentials of 2HNQ suggest that it may be a potential target for the management of diabetes mellitus.